If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -3(2x + -3) = -4 Reorder the terms: 8 + -3(-3 + 2x) = -4 8 + (-3 * -3 + 2x * -3) = -4 8 + (9 + -6x) = -4 Combine like terms: 8 + 9 = 17 17 + -6x = -4 Solving 17 + -6x = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + -6x = -4 + -17 Combine like terms: 17 + -17 = 0 0 + -6x = -4 + -17 -6x = -4 + -17 Combine like terms: -4 + -17 = -21 -6x = -21 Divide each side by '-6'. x = 3.5 Simplifying x = 3.5
| x^2+4x+7=6 | | y-2=x/3 | | 14-4(3x-5)=-6 | | -2=g-16/-1 | | 5-x/67 | | 12y+25=-35You | | (6+y)+y=60 | | -10-19n=-18n | | 3y-6=y+6(-2) | | X+y+y=60 | | -8ac^2(3c^3+5a^4-2)= | | 3y-6=y+6 | | p^2/3-p^1/3=6 | | 4b-3=7b | | (2b+9)=3 | | x+5+3x-7=180 | | 2(x-3)=2x+15 | | -3=x/-3-2 | | 3x+2x^2+5x= | | -9+11p=19+13p | | 5/12x4 | | 7x^2-14x+10=3 | | 14/(2-x | | 13q-2=-19+14q | | 9n^2=5+4n | | 50=28.1+.15m | | 12z-10z-2=2 | | 5x+6x-2x=43+2 | | rv+3*1v-3=0 | | 7-2.5x=13 | | 1.09(1.23)(7-x)=9 | | (X-28)+(2x-79)+(.5x+14)=180 |